The unseen diversity of the semi-aquatic earthworms of the genus Sparganophilus (Oligochaeta: Sparganophilidae) from the Southeastern Appalachian Piedmont - Carrera-Martínez, Roberto; Taylor, Melanie K.; Jones, Daniel; Schoville, Sean D.; Snyder, Bruce A.; Callaham, Mac A. (Zootaxa, 2025)
After one year of surveying semiaquatic earthworms (Oligochaeta, Sparganophilidae), we describe Sparganophilus jenkinsi sp. nov., S. carveri sp. nov., S. oconeeae sp. nov., S. williamsae sp. nov., S. muskogee sp. nov., S. youngae sp. nov., and S. borgesae sp. nov. based on extensive differences in morphological characters and molecular data. Three additional species are described morphologically but not formally named due to limited material. The species of Sparganophilus described here can be organized into three species groups: (1) S. jenkinsi, S. oconeeae, S. muskogee, S. carveri, S. williamsae, S. youngae, S. borgesae, and Sparganophilus sp02 have continuous tubercula pubertatis in the region of xvii–xxii, and tubular nephridial bladder; (2) Sparganophilus sp09 have three discrete pairs of tubercula pubertatis and sack-like nephridial bladder; and (3) Sparganophilus sp10 have the tubercula pubertatis posteriorly displaced and reduced to two segments, and have a nephridial “caecum.” These new species contribute to our knowledge of the endemism and biodiversity of earthworms in the Appalachian Piedmont.